Experimental study on the effect of frost parameters on domestic refrigerator finned tube evaporator coils - Ozkan, Derya Burcu; Ozil, Eralp (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
In this study, parameters affecting the frost formation on the evaporator of a refrigerator and the structure of frost were examined. Air velocity measurements both at the air inlet and outlet channels of the evaporator were performed, and the effect of air velocity on frost formation was examined. The rate of evaporation of water inside the refrigerator cabin was also recorded. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thermodynamics; Energy & Fuels; Engineering; Mechanics